2019
DOI: 10.15627/jd.2019.8
|View full text |Cite
|
Sign up to set email alerts
|

Daylight Transport Systems for Buildings at High Latitudes

Abstract: This paper is a literature study of daylight transport systems aiming at selecting the most appropriate ones for application at high latitudes. It is limited to the systems that transport light at a long distance from the façade and distribute it either in the building core or at a rear place in a room adjacent to the façade. The literature is spanning from the 80s' to the present. It covers the theoretical background and development of the systems from their infancy, through technical development of the desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 120 publications
(182 reference statements)
0
18
0
Order By: Relevance
“…This system transmits light from the roof to the underground space through a duct, which is equipped with a converging lens and tracking mirror (heliostat) to direct sunlight. Over the past three decades, innovations in light transmission systems have made great strides; However, these systems have both positive and negative challenges [39], and all aspects (performance, efficiency and commercially) [40] must be considered in order to make the right choice.…”
Section: Overview On the Light Transmission Systemsmentioning
confidence: 99%
“…This system transmits light from the roof to the underground space through a duct, which is equipped with a converging lens and tracking mirror (heliostat) to direct sunlight. Over the past three decades, innovations in light transmission systems have made great strides; However, these systems have both positive and negative challenges [39], and all aspects (performance, efficiency and commercially) [40] must be considered in order to make the right choice.…”
Section: Overview On the Light Transmission Systemsmentioning
confidence: 99%
“…In the literature review [20] has been showed the light efficiency of various components and light conductors for the entire lighting system. The auditory luminous flux of daylight, for various weather conditions and seasons throughout the year, has also been accounted in examined studies in accordance with the requirements for office lighting.…”
Section: Calmentioning
confidence: 99%
“…A review of the literature on daylight transport systems (DTS) revealed that light pipes could reduce the energy used for electrical lighting in commercial buildings at high latitudes by up to 30% [3 , 6 , 9 , 15] . In particular, horizontal daylight tubes mounted in the ceiling plenum have been promoted as a successful solution for a deeper daylighting supplement in multi-storey commercial buildings in locations far north or south [17] . Horizontally-mounted daylight tubes, unlike vertical light tubes, have a limited possibility to receive light from the zenithal part of the sky and will primarily base its light transmission efficiency on direct light from the sun.…”
Section: Introductionmentioning
confidence: 99%